Bimbingan Teknis Desain dan Penggunaan Alat Pencacah Nilam Sederhana untuk Meningkatkan Efisiensi dan Efektifitas Pengelolaan Nilam di Desa Opaasi Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Alimin, Alimin; Ismail, Darwin; Mashuni, Mashuni; Ritonga, Halimahtussaddiyah; La Agusu, La Agusu; Zani, Munirwan; Rahmayanti, Rahmayanti; Muhamad, Fadel; Adman, Finkyasti Nur; Amal, Della Ardana; Anjani, Ika; Alham, Alham (Vokasi Universitas Halu Oleo, 2023)
Desa Opaasi is one of the villages where many residents work as patchouli farmers. In 2022, the previous PKM team assisted the community by organizing equipment for distillation and purification of patchouli oil. The main focus of the current program is on the processing of patchouli harvests by farmers who still use conventional methods, such as using a machete to chop their patchouli harvests, making the process ineffective and inefficient. The PKMI 2023 Team then designed and created a patchouli chopping tool as a solution to enhance the efficiency and effectiveness of farmers in chopping their patchouli harvests. Additionally, PKMI team showed technical guidance on the proper use and maintenance of the patchouli chopping tool was provided to the patchouli farmers to ensure optimal utilization and care.